Subtle East–West Phylogeographic Break of Asteropyrum (Ranunculaceae) in Subtropical China and Adjacent Areas - Shanmei Cheng; Weidong Zeng; Dengmei Fan; Hua Liang; Yi Yang; Yixuan Kou; Zhiyong Zhang (Diversity, 2021)
East–west phylogeographic break is common among plant species in subtropical China. However, the estimation time of east–west phylogeographic break has always relied on inferences of calibrated phylogenies, and the contribution of environmental heterogeneity to population differentiation has largely been ignored. In this study, we estimated the divergence time of Asteropyrum populations through coalescent-based approaches based on DNA sequences of ten nuclear loci and evaluated the contribution of environmental heterogeneity to population differentiation. The results showed that there were two chloroplast clades and nuclear groups within Asteropyrum, displaying a subtle pattern of east–west differentiation. The divergence time of the two nuclear groups was dated to ~1.2 Ma, which is associated with climate changes during the Mid-Pleistocene transition. A genetic admixture event between the two genetic groups happened at ~0.46 Ma, resulting in several admixed populations. Isolation by environmental distance (IBE) explained the majority (46.32%) of population differentiation, but that isolation by geographic distance (IBD) only contributed 4.66%. The results of this study suggest that climate changes during the Pleistocene may be a major cause for the east–west phylogeographic break in subtropical China. However, the complex terrain and high environmental heterogeneity in the west of subtropical China (and adjacent regions such as the Hengduan Mountains and the Himalayan Moutains) caused by strong geological uplift may have profoundly shaped the population structure of plant species in subtropical China.